Toxicity spectrum of pegvaliase: A pharmacovigilance analysis using the FAERS database - Luyao Xu; Kaili Mao; Songyang Zhong; Huayu Sun; Hongliang Zheng; Zhenling Fu (Orphanet Journal of Rare Diseases)
Abstract Objective This research aimed to assess the safety of pegvaliase through analyzed the data from the FAERS database, thus providing a theoretical foundation for the rational and safe application of pegvaliase in clinical settings. Methods Pegvaliase-associated adverse event reports were searched in FAERS database from the 2018 Q3 to 2023 Q2. These data were further mined through Four different algorithms, including ROR, PRR, BCPNN, and EBGM. Results A total of 5,076 AEs reports were obtained from the FAERS database. At the PTs level, it was discovered that AE reports associated with pegvaliase as the primary suspect were connected to the 27 SOCs. Among these PTs, 83 signals in total were found, and each of them concurrently complied with the four algorithms. Further, we ranked PTs first for arthralgia in order of frequency and first for decreased amino acid levels in order of signal intensity. The median time to onset of adverse reactions was 15 days. Conclusion We mined and analyzed the AE signals of pegvaliase based on the FAERS database, it turned out that they were generally consistent with the drug inserts and clinical trial results. However, potential new AE signals were revealed, providing a basis for the identification of adverse reactions in the clinical setting.